Guillain Barre Syndrome - Acute Inflammatory Demyelinating Polyneuropathy with Unusual Descending Paralysis: Life Sciences-Medicine - Meera Devi, Dr Kannan; V Padma, Dr; Sathyapriya, Dr; Shiny Thomson, Dr; Sarath Bhaskar, Dr; Saketh Ramineni, Dr (International Journal of Life Science and Pharma Research, 2022)
Guillain-Barré syndrome (GBS) is a rare autoimmune, acute fulminant polyradiculoneuropathy. Incidence is between 1- 4 cases per 100,000 per year. It can affect age groups such as both young and old. The distribution depending on age-specificity appears to be bimodal, and has high rates in young adults as well as the elderly. Mostly manifests as rapidly evolving areflexic motor paralysis with a usual ascending type of paralysis. Autonomic involvement is common with usual manifestations of loss of vasomotor control such as BP fluctuations, postural hypotension, and arrhythmias. Deep tendon reflexes are diminished or disappear in the first few days of disease onset. Several cases have been reported with descending type of paralysis, but they were patients of Miller Fischer syndrome variant of GBS. Only 15% of the cases were reported regarding descending type of paralysis in AIDP variant of GBS. Our patient presented with unusual descending paralysis, starting with the upper limbs and progressively involving weakness of the lower limbs. The patient did not have any comorbid illnesses rather than recent gastrointestinal infections. In the progress of the disease, he developed respiratory complications for which he needed ventilator support and with all supportive care and keen monitoring, the patient was weaned off from the ventilator, a tracheostomy done, and improved. Thus presenting a case of Guillain Barre syndrome with an unusual descending type of paralysis and with all other typical symptoms of this condition, who have been treated with high dose IV immunoglobulin, creates awareness in view of diagnosing the disease even with unusual presentation would save the life of the patient, instead presenting the usual case scenario or rare disease case.